2021
DOI: 10.1093/ofid/ofab469
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of the Experience of Immediate Antiretroviral Therapy Among Urban Persons With Newly Diagnosed Human Immunodeficiency Virus

Abstract: Background Guidelines recommend immediate antiretroviral therapy (ART) at or shortly after HIV diagnosis, yet little is known about how people living with HIV (PLWH) experience this treatment strategy, including racial/ethnic minorities, cis/trans women, and those with housing instability. Methods To assess the acceptability of immediate ART offer among urban PLWH, understand how this approach affects the lived experience of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Another reason for this observation is that the rapid ART strategy may not provide enough time to address HIV stigma, social determinants of health, and medical mistrust, leading to loss to follow-up and lower medication adherence. This was observed in a qualitative study on the rapid ART strategy in San Francisco, which showed high acceptability but found that some patients hesitated to undergo rapid ART due to complex psychosocial and structural challenges [ 26 ]. Studies in South Africa, Ethiopia, and a large program in Sub-Saharan Africa have also shown that same-day ART initiation resulted in more loss to follow-up [ 13–15 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another reason for this observation is that the rapid ART strategy may not provide enough time to address HIV stigma, social determinants of health, and medical mistrust, leading to loss to follow-up and lower medication adherence. This was observed in a qualitative study on the rapid ART strategy in San Francisco, which showed high acceptability but found that some patients hesitated to undergo rapid ART due to complex psychosocial and structural challenges [ 26 ]. Studies in South Africa, Ethiopia, and a large program in Sub-Saharan Africa have also shown that same-day ART initiation resulted in more loss to follow-up [ 13–15 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, patient data from this study were analyzed separately [ 39 ], and without inferring direct links between meaningful care elements that patients reported and those intended by providers, we can broadly identify concordance across findings. Patient findings published in 2021 show that, in addition to the offer of the ART itself, patients valued the emotional support of the “ART encounter,” and that Rapid ART as a process helped offset patient fears [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Literature looking at rapid ART has found high uptake rates, in a variety of settings 8–10 12 13. Qualitative studies in the USA, Eastern Africa and South Africa show various barriers to and facilitators of uptake among people living with HIV and their healthcare professionals 14–23. Barriers include time to adjust to the new HIV diagnosis, shock, denial, fear of domestic violence, anticipated side-effects and logistical issues.…”
Section: Introductionmentioning
confidence: 99%
“…Barriers include time to adjust to the new HIV diagnosis, shock, denial, fear of domestic violence, anticipated side-effects and logistical issues. Facilitators such as wanting to improve health, a sense of agency, the benefits of viral suppression and provider knowledge and attitudes have been reported 14–23…”
Section: Introductionmentioning
confidence: 99%